A Single Electronic Tattoo for Multisensory Integration. Issue 4 (21st February 2023) - Wang, Zheng; Zhou, Zhi; Li, Chen‐Long; Liu, Xiao‐Hao; Zhang, Yue; Pei, Man‐Man; Zhou, Zheng; Cui, Da‐Xiang; Hu, Dong; Chen, Feng; Cao, Wen‐Tao
Abstract: Wearable electronics are garnering growing interest in various emerging fields including intelligent sensors, artificial limbs, and human–machine interfaces. A remaining challenge is to develop multisensory devices that can conformally adhere to the skin even during dynamic‐moving environments. Here, a single electronic tattoo (E‐tattoo) based on a mixed‐dimensional matrix network, which integrates two‐dimensional MXene nanosheets and one‐dimensional cellulose nanofibers/Ag nanowires, is presented for multisensory integration. The multidimensional configurations endow the E‐tattoo with excellent multifunctional sensing capabilities including temperature, humidity, in‐plane strain, proximity, and material identification. In addition, benefiting from the satisfactory rheology of hybrid inks, the E‐tattoos are able to be fabricated through multiple facile strategies including direct writing, stamping, screen printing, and three‐dimensional printing on various hard/soft substrates. Especially, the E‐tattoo with excellent triboelectric properties also can serve as a power source for activating small electronic devices. It is believed that these skin‐conformal E‐tattoo systems can provide a promising platform for next‐generation wearable and epidermal electronics. Abstract : A single electronic tattoo (E‐tattoo) based on a mixed‐dimensional matrix network that integrates two‐dimensional MXene nanosheets in conjunction with one‐dimensional cellulose nanofibers and Ag nanowires has been developed for multisensory integration. The multidimensional configurations endow the E‐tattoo with excellent multifunctional sensing capabilities including temperature, humidity, in‐plane strain, proximity, and material identification.